Gotong Royong Sebagai Sarana Dalam Upaya Mempererat Solidaritas Masyarakat Desa Benuang Kecamatan Talang Ubi - Anggy Utama Putri; Ahmad Apriyanto; Ameylia Ameylia; Icha Puji Tifanila; Maryana Maryana; Rima Dinata (JURNAL PENGABDIAN KADER BANGSA, 2026)
This study aims to examine how the role of solidarity between communities works and of course is supported by how the community responds to each value in mutual cooperation embedded in their environment. Community responses to these values ​​vary, adjusted to the level of solidarity felt. The method used in writing this article is a literature review, which involves searching for information from various sources such as research journals, journal reviews, and data related to mutual cooperation practices in Benuang Village. The results of the study indicate that mutual cooperation activities carried out in this village can foster a sense of mutual assistance and strengthen bonds between residents, which indirectly strengthens their solidarity to continue to collaborate and maintain the culture and moral values ​​contained in the mutual cooperation activities.